Studi Karakteristik Kekuatan Tarik Dan Harga Impak Material Polymeric Foam Sandwich Panels Komposit Dengan Variasi Perlakuan Serat Tandan Kosong Sawit - Rahmat, Ridho Zarli; Badri, Muftil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This study refers to the characteristic studies of tensile strength and impact rates of polymeric foam materials composite sandwich panels and variations in the treatment of empty palm bunch fibers. This research is done by making specimen with different fiber treatment which then will be tested tensile strength and impact price to be analyzed. The results of the analysis in the study will be evaluated and compared each other. The purpose of this research is to obtain a board that can absorb impact energy and which has tensile strength. In the manufacture of sandwich panels specimen is done by varying the boiling of fiber, fiber counting and long fiber counting. The composite obtained is a plate with a thickness of 3 mm. The number of specimens made was 42 specimens. Composite specimens with TKS fiber boiling treatment in aquades with enumeration (counting) does not affect the value of the ultimate tensile strength, but increasing the value of the impact price and decreasing as the enumeration took place. Composite specimens with TKS fiber immersion treatment in NaOH solution with enumeration decreased the value of the ultimate tensile strength during the enumeration time, but did not affect the value of the impact price. Composite specimens with TKS fiber boiling treatment with enumeration did not affect the value of ultimate tensile strength and composite impact price.Keywords :Ploymeric Foam, Fiber treatment, Sandwich Panels, Empety palm bunch fibers.